2018
DOI: 10.1016/j.bbagen.2018.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical and structural effects of (2R,6R)-hydroxynorketamine on the mitochondrial metabolome in PC-12 cells

Abstract: The present data provide an overall view of the metabolic changes in mitochondrial function produced by (2R,6R)-HNK and related ketamine compounds and offer an insight into the source of the observed variance in antidepressant response elicited by the compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 80 publications
(128 reference statements)
0
12
0
Order By: Relevance
“…A number of HNK metabolites have been described, including the (2,4)-, (2,5)-, and Mouse, rat, and dog bioavailability and mouse oral antidepressant efficacy of (2R,6R)-hydroxynorketamine (2,6)-HNKs, (Desta et al, 2012;Moaddel et al, 2010;Woolf and Adams, 1987), with (2R,6R;2S,6S)-HNK being the most prevalent in the plasma of humans (Zarate et al, 2012) and in the plasma and brain of rodents (Can et al, 2016;Moaddel et al, 2016;Zanos et al, 2016) following ketamine administration. Although early studies classified (2R,6R;2S,6S)-HNK as an inactive metabolite due to its lack of anesthetic effects (Leung and Baillie, 1986), more recent studies have established the biological activity of this metabolite (Cavalleri et al, 2018;Chou et al, 2018;Faccio et al, 2018;Ho et al, 2018;Kroin et al, 2018;Moaddel et al, 2013;Paul et al, 2014;Pham et al, 2017;Singh et al, 2016;Wray et al, 2018;Yao et al, 2017;Zanos et al, 2016). Notably, it has been demonstrated that, in mice and rats, intraperitoneal (i.p.)…”
mentioning
confidence: 99%
“…A number of HNK metabolites have been described, including the (2,4)-, (2,5)-, and Mouse, rat, and dog bioavailability and mouse oral antidepressant efficacy of (2R,6R)-hydroxynorketamine (2,6)-HNKs, (Desta et al, 2012;Moaddel et al, 2010;Woolf and Adams, 1987), with (2R,6R;2S,6S)-HNK being the most prevalent in the plasma of humans (Zarate et al, 2012) and in the plasma and brain of rodents (Can et al, 2016;Moaddel et al, 2016;Zanos et al, 2016) following ketamine administration. Although early studies classified (2R,6R;2S,6S)-HNK as an inactive metabolite due to its lack of anesthetic effects (Leung and Baillie, 1986), more recent studies have established the biological activity of this metabolite (Cavalleri et al, 2018;Chou et al, 2018;Faccio et al, 2018;Ho et al, 2018;Kroin et al, 2018;Moaddel et al, 2013;Paul et al, 2014;Pham et al, 2017;Singh et al, 2016;Wray et al, 2018;Yao et al, 2017;Zanos et al, 2016). Notably, it has been demonstrated that, in mice and rats, intraperitoneal (i.p.)…”
mentioning
confidence: 99%
“…There is some evidence indicating that HNKs can alter mitochondrial function and energy metabolism, which may contribute to their antidepressant actions; namely, using a metabolomics approach, Faccio et al (2018) demonstrated that a 36-hour exposure of PC12 cells to (2R,6R)-HNK (5 nM) and, to a lesser extent, (2S,6S)-HNK (0.5 nM), (R)-, and (S)ketamine (1 mM) altered the mitochondrial metabolome. Specifically, at the concentrations tested, (2R,6R)-HNK robustly increased markers of glycolysis, including glycerate, fructose-6-phosphate, and glucose-6-phosphate.…”
Section: Effects On Mitochondrial Function and Energy Metabolismmentioning
confidence: 99%
“…There are additional reports demonstrating that (2R,6R)-HNK increases the release of other neurotransmitters, including serotonin and norepinephrine (Ago et al, 2019), and promotes structural plasticity via dendritic outgrowth (Cavalleri et al, 2018;Collo et al, 2018). Recently, (2R,6R)-HNK was also shown to affect other processes, such as inflammatory responses (Ho et al, 2019;Xiong et al, 2019;Rahman et al, 2020) and mitochondrial function (Faccio et al, 2018;Rahman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…5A/B/C/D). The TCA cycle, purine metabolism, and glutamate metabolism were selected as the crucial metabolic pathways according to the number of metabolites contained in metabolic pathways and the relationship between metabolic pathways [34] (Fig. 5E).…”
Section: Ssa and Af Protected Corticosterone-induced Neuroinjury By Rmentioning
confidence: 99%
“…Studies have shown that corticosterone, Aβ 25−35 , and (2R,6R)-Hydroxynorketamine could induce disturbance of cellular metabolic, including purine metabolism, glutamate metabolism, and TCA cycle, etc. in PC12 cell [25][26][27][28]. Meanwhile, metabolomics is an effective tool to elucidate the potential compatibility mechanisms of traditional Chinese medicine [29].…”
Section: Introductionmentioning
confidence: 99%